Seeing Is Feeding for the Frugivorous Bird Brown-Eared Bulbul (Microscelis amaurotis) - Takeshi Honda; Jun-ichi Tsuboi; Hiroshi Kuwata (International Journal of Zoology)
We examined feeding behavior by visually blocking fruit to establish a new theory of bird damage management for agricultural practices. Partly or fully invisible clusters of grapes were fixed on a perch. The birds selectively pecked the clearly visible part of the half-visible bag at a pecking count rate of 0.94–1.00 (95% CI). Half-visible bags allowed the birds to look inside like a skirt and detect the initially hidden portions of grapes, which were covered with opaque white bags. However, very few birds pecked at the white bags that were partially covering the grapes. That is, very few birds attempted to eat covered but easily detectable fruits. Only five birds gravitated toward the grapes in the completely covered nontranslucent bags, but they never pecked at them. Our results show that visual blocking could be a promising new technique to prevent bird damage.